Clinical and Endoscopic Features of Pneumatosis Cystoides Intestinalis: A Retrospective Study in 192 Patients - Yan Wang,; Yan Wang,; Bo Zhang,; Longsong Li,; Hongyi Sun,; Hongyi Sun,; Ningli Chai, (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Pneumatosis cystoides intestinalis is not well recognized. Clinical features vary in several case reports, and prognosis remains unclear. We aimed to summarize the clinical and endoscopic features of pneumatosis cystoides intestinalis and to explore potential factors associated with lesion size. Materials and Methods: We retrospectively collected clinical and endoscopic features of patients diagnosed with pneumatosis cystoides intestinalis from July 2015 to October 2021. Patients were allocated to 2 groups according to lesion size with 2 cm as boundary value. Baseline characteristics were compared between the groups. Results: A total of 192 patients were included in this study with a 1.3:1 male-to-female ratio. About 91 lesions (47.70%) were ≥2 cm and those patients were more likely to have a history of polypectomy or abdominal surgery compared to lesion size <2 cm (P < .05). For 50 patients who received follow-up colonoscopy, 28 cases (56.00%) disappeared spontaneously and 22 cases (44.00%) remained unchanged. No factors have been observed to be connected with prognosis. Conclusions: Colonoscopy is beneficial to the diagnosis of pneumatosis cystoides intestinalis. Patients with a history of polypectomy or abdominal surgery were more likely to develop lesions <2 cm. Most patients do not need special treatments and have favorable prognosis. Cite this article as: Wang Y, Zhang B, Li L, Sun H, Chai N, Linghu E. Clinical and endoscopic features of pneumatosis cystoides intestinalis: A retrospective study in 192 patients. Turk J Gastroenterol. 2023;34(11):1116-1123.